Indonesia PENGARUH UKURAN PARTIKELTERHADAP SIFAT FISIK DAN MEKANIK KOMPOSIT LIMBAH GERGAJI KAYU JATI DENGAN MATRIK RESIN EPOXY: PENGARUH UKURAN PARTIKELTERHADAP SIFAT FISIK DAN MEKANIK KOMPOSIT LIMBAH GERGAJI KAYU JATI DENGAN MATRIK RESIN EPOXY - rita desiasni; Fauzi Widyawati; Riza Monica (Fakultas Teknologi Lingkungan dan Mineral - Universitas Teknologi Sumbawa, 2022)
The physical and mechanical properties of particle composite materials are influenced by particle size. Variations in particle size will form different physical and mechanical properties. The size variations used are 100 mesh, 150 mesh, 200 mesh. The comparison between matrix and particles is 70% : 30% using the hand lay-up method. The test consists of physical tests, namely density and thickness expansion as well as mechanical tests consisting of Modulus Of Rapture (MOR) and Modulus Of Elasticity (MOE). The results of the physical density test were at a value of 0.93-1.02 g/cm3, the best density was at a particle size of 100 mesh with a value of 1.02 g/cm3. While the thickness test obtained values ??ranging from 9.3-9.8%, with the highest thickness development of 9.8% at a particle size of 100 mesh. While the results of the mechanical test itself, all variations in mesh size meet the standard, namely the highest MOR test is obtained in the 100 mesh variation, with a value of 341.15 kgf/cm2, while in the MOE test none of which meets the standards of SNI 03-2105-2006, the highest mesh variation is obtained by mesh. obtained at mesh 100 that is 8072.49 kgf/cm2.